Management of the local relapse of the bladder – prostate rhabdomyosarcoma - Spychała, Marcelina; Maroszek, Grzegorz; Kawalec, Agata; Godziński, Jan (Pediatria Polska - Polish Journal of Paediatrics, 2022)
Introduction: Rhabdomyosarcoma (RMS) is the most common soft-tissue sarcoma in children. Genitourinary locations occur in approximately 20–30% of cases. Children with RMS localized in the bladder or/and prostate require multi-modal therapy with systemic chemotherapy in conjunction with surgery or radiation therapy to maximize local tumour control. Material and methods: The report presents a case of a 3-year-old boy diagnosed in 2015 with embryonal RMS, who was treated due to relapse of RMS in the urinary bladder in 2016–2018. The patient was treated with chemotherapy, radiotherapy, and surgery (the urinary bladder was excised, and a neobladder was created according to Florida-pouch procedure). Currently, the patient is in the 3rd year of observation after the end of oncological treatment Conclusions: The treatment for RMS localized in the bladder puts the priority on organ-sparing techniques. Radiotherapy or brachytherapy are standard supplementary treatments. However, in the case of relapse, mutilating rescue surgery still has value.